Finite Element Vibration and Dynamic Response Analysis of Engineering Structures - Jaroslav Mackerle (Shock and Vibration)
This bibliography lists references to papers, conference proceedings, and theses/dissertations dealing with finite element vibration and dynamic response analysis of engineering structures that were published from 1994 to 1998. It contains 539 citations. The following types of structures are included: basic structural systems; ground structures; ocean and coastal structures; mobile structures; and containment structures.